Manufacturing Performance: Industrial City to Superior in Competitive Advantage - Sarjana, Sri; Khayati, Nur (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
Competitive Advantage (CA) is defined as a company's strategy to create value of product or service that has uniqueness and distinctiveness to be beneficial for customers if compared to other competitors. This study empirically investigated whether the effects of manufacturing capability, dynamic capabilities, manufacturing performance, and competitive advantage on business development. The authors conducted a survey to test the hypotheses and designed a SEM to analyze them. The results showed that the manufacturing capability and dynamic capabilities were effective in influencing manufacturing performance. Manufacturing capability and dynamic capabilities were effective and directly influenced on competitive advantage. Moreover, this study demonstrated that the effect of competitive advantage was mediated by manufacturing performance. This finding integrated the insights in manufacturing performance framework into a generalization of the competitive advantage in industrial city. Furthermore, this research was expected to provide information for management at industrial city that had valuable suggestions for management practices to increase manufacturing performance and achieved the manufacturing goals especially in competitive advantage.